(untitled) (The Pakistan Development Review, 2019)
This study uses the Pakistan Rural Household Survey 2004-5 (PRHS), a rich set of households and school data, to examine parents’ schooling decision in rural Pakistan. Nested logit regressions are used to quantify the determinants of child school attendance. The analysis confirms that the greater the number of schools (public or private) in the local communities the higher is the attendance. Lower school attendance of boys seems to be the outcome of lower school quality more than it is for girls. A marginal increase in school quality correlates with increased school attendance in government schools more than in private schools. Nearly all school quality variables including control for number of schools in a community stand insignificant for girls. This shows that other factors might be of more importance than school quality of local schools for girl’s low attendance in rural Pakistan. Besides, parental education, especially mother’s education, and household income have strong positive impact on child school attendance. The greater the number of children in the household the lower is the child school attendance. Credit constraint seems not to be problematic as the estimated effect is statistically insignificant. The size of landholding seems to be important only in the case of girls schooling. JEL Classification: I21, I25, D13, C25 Keywords: Demand for Schooling, Public Education, Private Education, Pakistan